THE STRATEGIC ROLE OF MADRASAH SELF-EVALUATION (EDM) IN THE OPTIMIZATION OF QUALITY ASSURANCE - Zaliva Lara Rozianti; Dhiyaa’ Ulfah; Sapuani Muhajir; Salfen Hasri; Sohiron (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Madrasah Self-Evaluation (EDM) is one of the essential instruments within the Internal Quality Assurance System (SPMI) that functions to measure, map, and continuously improve the quality of education in madrasahs. In practice, however, EDM implementation is still frequently regarded as a mere administrative activity, resulting in evaluation outcomes that have yet to be optimally utilized as a basis for decision-making and institutional development planning. This study aims to analyze the strategic role of EDM in optimizing madrasah quality assurance. The research method employed is library research, with data analyzed through content analysis techniques. The findings indicate that EDM plays a strategic role as an instrument for quality mapping, identification of institutional strengths and weaknesses, and a foundation for the preparation of the Madrasah Work Plan (RKM) and Madrasah Work and Budget Plan (RKAM). Furthermore, EDM supports data-driven decision-making, the strengthening of a quality culture, and continuous improvement in educational management. Optimization of EDM implementation can be achieved through enhancement of human resource competencies, strengthening of the Madrasah Quality Assurance Team, utilization of digital technology, and increased stakeholder participation. Accordingly, EDM functions not merely as an evaluative instrument, but also as a critical strategy in realizing effective, accountable, and quality-oriented madrasah governance on a sustainable basis.